Clinical vitamin-A deficiency and associated factors among pregnant and lactating women in Northwest Ethiopia: a community-based cross-sectional study - Abebaw Baytekus; Amare Tariku; Ayal Debie (BMC, 2019)
Abstract Background Vitamin A deficiency is known for its adverse health consequences, such as blindness, growth retardation and death. To curb the problem, Ethiopia has implemented various public health measures although little has been done to examine the deficiency among pregnant and lactating women. As a result, this study assessed the prevalence of Vitamin A deficiency and associated factors among pregnant and lactating women in Lay Armachiho district, northwest Ethiopia. Methods A community-based cross-sectional study was conducted on pregnant and lactating women in Lay Arimachiho district, northwest Ethiopia, using the multistage systematic sampling technique to select participants. The binary logistic regression model was fitted to test the effect of exposure variables, and the Adjusted Odds Ratio (AOR) with a 95% Confidence Interval (CI) and p-value < 0.05 were computed to identify the significance and the strength of the associations of variables with Vitamin A deficiency. Results The study revealed that 13.7% of the pregnant and lactating women had night blindness and 0.4% had also Bitot's Spot. Over 35 years of age of mothers (AOR = 2.74; 95%CI: 1.15,7.43), less than USD 22.7 household monthly income (AOR = 8.9; 95%CI: 4.54,21.73), and poor hand washing practices after toilets (AOR = 8.87; 95% CI: 4.43,18.68) were positively associated with VAD, while mothers' access to the media (AOR = 0.20; 95%CI:0.07, 0.59), formal education (AOR = 0.09; 95% CI: 0.03, 0.41), over 18 years of age at first marriage (AOR = 0.19; 95%CI: 0.08,0.36), and no fasting (AOR = 0.14; 95%CI: 0.04,0.46) were negatively associated. Conclusions Maternal Vitamin A deficiency was the major public health problem in Lay Armachiho district. Over 35 years of age of mothers, less than USD 22.7 household monthly income and poor hand washing practices after toilets were high risks for VAD, while mothers' access to the media, formal education, over 18 years at first marriage, and no fasting were low risks. Therefore, community awareness about the risk of early marriage, poor hand hygiene practices after toilets, and fasting during pregnancy and lactating period were essential. Organizations working on maternal health need to focus on mothers with low incomes in order to reduce their deficiency in Vitamin A.